ANALISIS PENERAPAN E-PLANNING DAN E-BUDGETING PADA PEMERINTAH DAERAH (STUDI KASUS PADA PEMERINTAH KABUPATEN BENGKALIS) - Virgiana Ningsih; Ria Nelly Sari; Muhammad Rasuli (Jurnal Ekonomi, 2018)
This research focuses on the aplication of the e-planning an e-budgetingin Bengkalis Regency as the purpose to describe, analyze and see more the factors of the less succesful implementation of e-planning and e-budgeting. So it becomes the constrain in planning and budgeting process in the goverment of Bengkalis Regency, as well as to know the respond of user of the application of e-planning and e-budgeting. This research was conducted in goverment agencies of Bengkalis Regency related to the planning and budgeting process area. This research was conducted with depth interview with party or officials that competent in the field of planning and budgeting, and also by collecting the data in Bappeda of Bengklis Regency. As result, there are several factors that make the application of e-planning and e-budgeting, they are human resources, ifrastructure, regulation and the applicatin it sefi.